Efficient Red Light Emitting Diodes Based on a Zero‐Dimensional Organic Antimony Halide Hybrid. Issue 9 (3rd January 2023) - Liu, He; Shonde, Tunde Blessed; Gonzalez, Fabiola; Olasupo, Oluwadara Joshua; Lee, Sujin; Luong, Derek; Lin, Xinsong; Vellore Winfred, J.S. Raaj; Lochner, Eric; Fatima, Iqra; Hanson, Kenneth; Ma, Biwu
Abstract: Zero‐dimensional (0D) organic metal halide hybrids (OMHHs) have recently emerged as a new class of light emitting materials with exceptional color tunability. While near‐unity photoluminescence quantum efficiencies (PLQEs) are routinely obtained for a large number of 0D OMHHs, it remains challenging to apply them as emitter for electrically driven light emitting diodes (LEDs), largely due to the low conductivity of wide bandgap organic cations. Here, the development of a new OMHH, triphenyl(9‐phenyl‐9H‐carbazol‐3‐yl) phosphonium antimony bromide (TPPcarzSbBr4 ), as emitter for efficient LEDs, which consists of semiconducting organic cations (TPPcarz + ) and light emitting antimony bromide anions (Sb2 Br8 2− ), is reported. By replacing one of the phenyl groups in a well‐known tetraphenylphosphonium cation (TPP + ) with an electroactive phenylcarbazole group, a semiconducting TPPcarz + cation is developed for the preparation of red emitting 0D TPPcarzSbBr4 single crystals with a high PLQE of 93.8%. With solution processed TPPcarzSbBr4 thin films (PLQE of 86.1%) as light emitting layer, red LEDs are fabricated to exhibit an external quantum efficiency (EQE) of 5.12%, a peak luminance of 5957 cd m −2, and a current efficiency of 14.2 cd A −1, which are the best values reported to date for electroluminescence devices based on 0D OMHHs. Abstract : A highly luminescent zero‐dimensional (0D) organic antimony bromide hybrid containing semiconducting organic cation is developed for the first time, with which electrically driven red light emitting diodes (LEDs) are fabricated to exhibit an external quantum efficiency (EQE) of 5.12%, a peak luminance of 5957 cd m −2, and a current efficiency of 14.2 cd A −1 .